Formation of (14)C-Labeled Alanine from Pyruvate during Short Term Photosynthesis in a C(4) Plant - Kennedy, R. A. (1974)
Large amounts of alanine are produced in the first few seconds of photosynthesis in Portulaca oleracea L. The normal precursor-product relationship (phosphoglyceric acid → pyruvate → alanine) does not appear to operate in this species since labeling in pyruvate precedes that in phosphoglyceric acid. Pulse-chase experiments show that the alanine is rapidly metabolized. After a 6-second pulse of (14)CO(2), the percentage of (11)C in alanine drops more than 30% in the first 10 seconds of a (12)CO(2) chase period. The percentage of (14)C in the other early-labeled photosynthetic products, aspartate and malate, also decreases during the (12)CO(2) chase. The decrease of label in these compounds is concomitant with an increase in the labeling of sucrose and alanine, which in this case is formed via phosphoglyceric acid. Randomization of label within alanine increases gradually throughout the 2-minute chase. Alpha-keto acids accounts for up to 20% of the total (14)CO(2) incorporated by young leaf tissue. Pyruvate alone accounts for at least 65% of the radioactivity in the keto acid fraction in both young and mature leaves. Other early-labeled keto acids are oxaloacetate and, in young tissue only, hydroxyphenylpyruvate. We propose that, in Portulaca, pyruvate is one of the earliest-labeled photosynthetic products and serves as the immediate precursor of alanine.